1992
DOI: 10.1063/1.858299
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent deposition and trapping of aerosols at a wall

Abstract: The trajectories of aerosols are computed in a high-resolution direct numerical simulation of turbulent flow in a vertical channel. The aerosol equation of motion includes only a Stokes drag force and the influence of the aerosols on the gas flow is assumed to be negligible. Since the flow is vertical, aerosols deposit as a consequence of the turbulent fluctuations and their own inertia. It is shown that the eddies which are responsible for aerosol deposition are the same eddies that control turbulence product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(60 citation statements)
references
References 13 publications
4
56
0
Order By: Relevance
“…3(b), we observe that particle number density profile has developed a maximum well into the near-wall region (0 < z + < 20). This behavior can be viewed as the consequence of the turbulence non-homogeneity [50], and has been observed in a number of previous works [5,36,41].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…3(b), we observe that particle number density profile has developed a maximum well into the near-wall region (0 < z + < 20). This behavior can be viewed as the consequence of the turbulence non-homogeneity [50], and has been observed in a number of previous works [5,36,41].…”
Section: Introductionmentioning
confidence: 98%
“…There is experimental and numerical evidence that heavy particles in turbulent boundary layer have a tendency to migrate toward the wall under the turbophoretic drift [5,8,39,50,67]. Fig.…”
Section: Particle Dynamicsmentioning
confidence: 99%
“…Brooke et al (1992) and Brooke et al (1994) conducted Lagrangian particle tracking in a DNS-generated vertical channel flow with particles in the diffusion-impaction regime considering only the drag force. The paper by Brooke et al (1992) contains observations similar to those reported in other simulation work.…”
Section: 56b Lagrangian Simulations With Turbulent Flow From Les mentioning
confidence: 99%
“…Brooke et al (1992) and Brooke et al (1994) conducted Lagrangian particle tracking in a DNS-generated vertical channel flow with particles in the diffusion-impaction regime considering only the drag force. The paper by Brooke et al (1992) contains observations similar to those reported in other simulation work. These include the accumulation of particles in the diffusion-impaction regime near the vertical wall and their segregation into the low-speed streaks, the violation of the particle Reynolds number criteria for drag calculation, the importance of near-wall vortices in causing particle deposition and impact velocities of depositing particles on the same order as the friction velocity.…”
Section: 56b Lagrangian Simulations With Turbulent Flow From Les mentioning
confidence: 99%
“…A computational proce-dure for analyzing particle transport and deposition in complex passages was described by Li et al (1994). Using a direct numerical simulation procedure via a pseudospe ctral code, McLaughlin (1989), Ounis et al (1991bOunis et al ( , 1993, Brook et al (1992), Pedinotti et al (1992), and Squire s and Eaton (1991) analyzed the aerosol particle deposition in a turbulent channel¯ow. Soldati et al (1993) used a direct numerical simulation to study the particle transport in electrostatic precipitators.…”
Section: Introductionmentioning
confidence: 99%